Experimental Endoscope Rotitome-G: A pixel-by-pixel erasure microsurgical endoscopic sarcotome for resection of soft tissue tumours in closed body cavities - Gandhi, Harjeet Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2022)
Background: The procedure of minimal access to the brain through the nose is an ancient practice. However, endoscopic entry via a burr hole has recently gained significant traction in the practice of neurosurgery. High-resolution endoscopic images are possible with limited admittance of accessory tools and instruments. Although brain tissue can be removed easily with a suction device, but it will be uncontrolled ‘excision’. The Rotitome-G is a precision micro-endoscopic target access surgical instrument. It has several accessories for intraoperative assessment and precise removal of the soft tissue lesions pixel-by-pixel within a closed body cavity through a single portal. Objective: This preliminary theoretical research study on Rotitome-G is transition to experimental cadaveric and clinical studies. It describes the construction and mechanics of this newly conceptualized robot-assisted microsurgical endoscope. The design includes precise excision at the pixel and microscopic level and removes tissue debris under computer-aided navigation and direct instrument vision. Currently, the primary objective is to interest both the neurosurgeons and biomedical engineers, hence its contents are diverse resulting in an extended text. Methodology: The study provides the basics of computer vision techniques and neuronavigation to establish the function and application of the Rotitome-G. The structure and kinematics of the animalcule Rotifer have been considered followed by the construction of Rotitome-G. For a better understanding of intracranial tumour excision, the article examines the role of intra-operative imaging, biomechanics of brain tissue, and brain shift to better understand the principles of this newly conceived microsurgical instrument. The functional capabilities of the instrument have been putatively demonstrated by describing the excision of a glioblastoma. Conclusion: It is expected that the key design of Rotitome-G would meet the goal of neurosurgical resection by excising maximum amount of pathological tissue. Direct microscopic resection will prevent damage to the eloquent areas to improve the prognosis by limiting neurological morbidity. Clinical validity of the Rotitome -G remains to be determined.